Comparison between articular chondrocytes and mesenchymal stromal cells for the production of articular cartilage implants - Frerker, Nadine; Karlsen, Tommy A.; Stensland, Maria; Nyman, Tuula A.; Rayner, Simon; Brinchmann, Jan E. (Frontiers in Bioengineering and Biotechnology, 2023)
Focal lesions of articular cartilage give rise to pain and reduced joint function and may, if left untreated, lead to osteoarthritis. Implantation of in vitro generated, scaffold-free autologous cartilage discs may represent the best treatment option. Here we compare articular chondrocytes (ACs) and bone marrow-derived mesenchymal stromal cells (MSCs) for their ability to make scaffold-free cartilage discs. Articular chondrocytes produced more extracellular matrix per seeded cell than mesenchymal stromal cells. Quantitative proteomics analysis showed that articular chondrocyte discs contained more articular cartilage proteins, while mesenchymal stromal cell discs had more proteins associated with cartilage hypertrophy and bone formation. Sequencing analysis revealed more microRNAs associated with normal cartilage in articular chondrocyte discs, and large-scale target predictions, performed for the first time for in vitro chondrogenesis, suggested that differential expression of microRNAs in the two disc types were important mechanisms behind differential synthesis of proteins. We conclude that articular chondrocytes should be preferred over mesenchymal stromal cells for tissue engineering of articular cartilage.